2012
DOI: 10.1097/mlr.0b013e31826c84e1
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Response to Patient Experience Measures in Complex Information Environments

Abstract: Participants presented with CAHPS information and other performance indicators relied less on CAHPS than did those presented with CAHPS information only, although they considered CAHPS information as valuable as did other respondents. Participants presented with smaller choice sets also judged CAHPS information as less easy to use when accompanied by other metrics than when it was presented alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Further, our completion rate is typical of internet surveys that target samples representing the population on key demographic criteria. 26,41,42,43 Although individuals who earn less and have less formal education were under-represented, bivariate analyses demonstrated that the attitudes and beliefs examined did not differ significantly along these characteristics (data not shown). Further, our findings on the predictors of reduced obligations to participate in WG/ES-based NBS were based on a smaller sub-sample of 472 and should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 95%
“…Further, our completion rate is typical of internet surveys that target samples representing the population on key demographic criteria. 26,41,42,43 Although individuals who earn less and have less formal education were under-represented, bivariate analyses demonstrated that the attitudes and beliefs examined did not differ significantly along these characteristics (data not shown). Further, our findings on the predictors of reduced obligations to participate in WG/ES-based NBS were based on a smaller sub-sample of 472 and should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, although there is ongoing debate about the relationship between PE measures and care quality, 37 -40 there is widespread agreement that PE is an important outcome in its own right, and these scores may be of greater interest to consumers. 13 Although women did not explicitly state that the absence of PE data was a concern, by guest on May 9, 2018 http://pediatrics.aappublications.org/ Downloaded from years, HEDIS and similar measures have been made publicly available, providing consumers with direct access to performance data on quality at the health plan, medical group, and practice level. Although these data are imperfect, in most cases they are the only information (other than anecdotal information or Yelp-type ratings) available to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Even when consumers are motivated to learn, the complexity of medical decision making may seem overwhelming for many of them. This is particularly true as public reports incorporate more measures of quality, cost, or other attributes of provider practices (Schlesinger, Kanouse, Rybowski, Martino, & Shaller, 2012). Under these circumstances, consumers will often focus on a smaller subset that seems most relevant to their choices and well-being.…”
Section: Factors Shaping Consumer Engagementmentioning
confidence: 99%
“…And since many will have no particular reason to think that quality varies substantially among providers, they may have little motivation to pay attention to quality metrics. They will likely view existing measures with less interest, understanding, or trust than will more "experienced consumers" (Schlesinger et al, 2012). Effective engagement will depend on strategies to make a case for the relevance of quality information and to offset or overcome that distrust.…”
mentioning
confidence: 99%